Analysis of Carbon Stocks in Mangrove Forest Areas in Padang City - Nanda, Popi; Yendri Sudiar, Nofi; Akmam, Akmam; Amir, Harman (Universitas Negeri Padang, 2023)
Global warming is caused by the disruption of the energy balance between the earth and the atmosphere. Carbon emission is the process of releasing greenhouse gases into the atmosphere due to human activities. High carbon emissions contribute to climate change. This climate change can have serious impacts on human life and ecosystems. Mangrove forests are one of the most carbon-rich forest types in the tropics. Mangrove areas are declining rapidly due to logging for the expansion of aquaculture ponds and infrastructure development. The data collection method used in this study is a survey method with field survey techniques (observation). Calculation of tree biomass and carbon stocks using allometric equations based on plant species and stem diameter.Carbon reserves in mangrove forests in general in the city of Padang amounted to 3,682.06 tonnes from 78 ha of mangrove forests. While the mangrove forest ditaluak buo can absorb 895.72 tonnes from 49 ha of mangrove forest. Based on carbon reserves, mangrove forests in the city of Padang are able to absorb 4,577.78 tons from 120 hectares of mangrove forest area in the city of Padang or around 38.90 ppm. Based on the results of the research, the value of Carbon Reserves in Taluak Buo is 4.97 tonnes / ha of 334 mangrove stems and is able to absorb or reduce carbon emissions by 18.28 tonnes / ha and the type of Sonneratia caseolaris is the largest contributor. Mangrove forests in Taluak Buo can absorb 9.45% of carbon emissions. The contribution of mangrove forests in the city of Padang is able to absorb 38.90 ppm while carbon emissions are 411.54 ppm. This means that the Mangrove Forest has not been able to clean up carbon emissions in the city of Padang and can be called that the city of Padang is a less healthy city